2020
DOI: 10.7150/ijbs.39351
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo biloba extract attenuates the disruption of pro-and anti-inflammatory T-cell balance in peripheral blood of arsenicosis patients

Abstract: Endemic arsenicosis is a public health problem that affects thousands of people worldwide. However, the biological mechanism involved is not well characterized, and there is no specific treatment. Exposure to arsenic may be associated with immune-related problems. In the present work, we performed an investigation to determine whether the Th17/Treg balance was abnormal in peripheral blood mononuclear cells (PBMCs) of patients with arsenicosis caused by burning coal. Furthermore, we investigated the effect of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 67 publications
3
23
0
Order By: Relevance
“…While, the ratio of Th17 to Treg cells in the 10 mg/kg NaAsO 2 was significantly increased by 164% compared to the baseline (Figure 2(D–F)). Combine with our previous study 15 that As exposure significantly disrupted the balance of Th17 and Treg cells as well as the corresponding cytokines IL‐17, IL‐6, and IL‐10 suggested that prolonged arsenic exposure might exhaust the immunoregulatory capacity of Treg subpopulations, ultimately resulting in Th17 predominant effects and disrupting the balance of pro‐inflammatory and anti‐inflammatory. Recent literature has indicated that the imbalance of Th17 and Treg cells is involved in the liver disease 12 .…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…While, the ratio of Th17 to Treg cells in the 10 mg/kg NaAsO 2 was significantly increased by 164% compared to the baseline (Figure 2(D–F)). Combine with our previous study 15 that As exposure significantly disrupted the balance of Th17 and Treg cells as well as the corresponding cytokines IL‐17, IL‐6, and IL‐10 suggested that prolonged arsenic exposure might exhaust the immunoregulatory capacity of Treg subpopulations, ultimately resulting in Th17 predominant effects and disrupting the balance of pro‐inflammatory and anti‐inflammatory. Recent literature has indicated that the imbalance of Th17 and Treg cells is involved in the liver disease 12 .…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, overexpression pro‐inflammatory mediators of TNF‐α and IL‐6 was also observed in chronic arsenic exposure individuals 47 . Our previous study also found that pro‐inflammatory cytokines IL‐6 and IL‐17A were higher in patients with arsenicosis 15 . In accordance with these observations, the present study showed that the concentration of pro‐inflammatory mediators IL‐6 and IL‐17 in sub‐chronic arsenic‐exposed rat's serum and liver were consistently increased compared with the control group.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations